A Descriptive Study On Questioning Skill In Past Tense Of The Seventh Grade Students At SMP NU Al-Amnan Bangorejo - Dian Agustria Islami; Wulan Wangi; Wiwin Indiarti (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2019)
The design of this research was descriptive quantitative study. The researcher used reading test as the instrument to get the research data. Population of the research was taken from the seventh grade students of SMP NU Al-Amnan Bangorejo 2015/2016 Academic Year, because there is only one class of the seventh grader. Based on the result of the test, the percentage score of the seventh grade students at SMP NU Al-Amnan Bangorejo are 60% students categorized as poor, 36% students categorized as good and 4% student categorized as excellent. One student who got the perfect score test had no difficulty in making interrogative sentences both using Verb2 and Tobe2. Nine students who got the good category in percentage of students reading test score having problems on the using Tobe2 (was and were) and have to add (–ed) in regular verb form and no (-ed) in irregular verb form. The rest of the 15 students who got poor category, facing problems on making interrogative sentences use Verb2 and Tobe2. Moreover, based on the researcher observation during the test, the rest 15 students did not do the tests independently.